The role of principal leadership in developing levels of resilience: a private senior secondary school ethnographic study - Yuda Saputra, Handika; Hidayati, Dian (Journal of Education and Learning (EduLearn), 2024)
This research is motivated by the level of school resilience which is not yet good, so school principals must increase school resilience with their leadership. Therefore, this research aims to analyze and describe the leadership of school principals in setting direction, developing human resources, and redesigning organizations to increase school resilience. The method used in this research is qualitative research with an ethnographic approach, which helps provide an in-depth and detailed picture of the school's daily habits in implementing school resilience. This research uses data collection techniques in the form of observation, interviews and documentation by carrying out data analysis techniques using description, analysis and interpretation. The results of this research explain that in carrying out the three leadership roles of the school principal, namely setting direction, developing people, and redesigning the organization, through school habits (culture), private schools will be able to create a level of resilience in the school environment. Even in unfavorable conditions, school principals can survive by carrying out leadership roles using existing school habits.